Bioterrorism: empower to respond - Azevedo, Ana Paula Chein Bueno de (2019)
The use of biological agents for the purpose of terrorizing enemies dates back many centuries. This terror action with the use of biological agents became popularized as Bioterrorism. Bioterrorist attacks are dangerous due to various factors involved, such as the silent way in which it may occur, or the type of biological agent that can be used depending on the purpose of the attack. To prevent contamination by these agents, the professionals who will act to combat these events should have knowledge about the varieties of mechanisms of actions and dissemination of the pathogens, as well the best way to neutralize and eliminate them; besides, they should have known how to choose appropriates protection equipment, both for individual and collective protection. Thus, it is necessary that such action teams be well empowered and trained. The purpose of this paper is to analyze, in the existing literature, what are the training modes in the world for first responders to attacks involving Chemical, Biological, Radiological or Nuclear (CBRN) agents. It is concluded that studies in this field are minimals and that more research and training for this kind of event should be carried out worldwide.